(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Organ transplantation represents one of the most transformative milestones in modern medicine. While Bangladesh achieved early success in kidney and corneal transplants, national progress has stagnated due to fragmented policy, inadequate infrastructure, and dependence on foreign centers. The tragic case of Dr. Shaila Nazneen Tania, a gynecologic oncologist who succumbed to cancer due to lack of access to liver transplantation, underscores the urgency of national reform. This article argues for the establishment of a Bangladesh National Organ Transplant Center (BNOTC), based on the existing Super Specialized Hospital (SSPH) at Bangladesh Medical University (BMU), to coordinate kidney, liver, and bone marrow transplantation services. A structured, autonomous, and merit-driven model can not only reduce medical migration and costs but also restore confidence in the country’s tertiary healthcare capacity. J Bangladesh Coll Phys Surg 2026; 44: 140-142